The economy and culture in the contemporary context - Santiesteban Leyva, Ernesto (Espergesia, 2015)
To argue about how these facts reveal the close relationship between culture and economy, the author analyzes the distinctive elements of the structural crisis of the capitalist system in the fields of economy and finances, environmental and ecological situation, social crisis, energy sphere and food situation. Theoretically, categories or concepts of economy and culture are defined, and the relevance of extending the scope of economic sciences to the realm of cultural phenomena is argued. Theoretical positions about these phenomena are briefly discussed, and the need to develop the Economy of Culture as a scientific discipline is evaluated taking into account the weight of the international art market and cultural industries in contem-porary life.